Ultraviolet adhesive as well as preparation method and application thereof
By using ultraviolet adhesives prepared by modified polyurethane acrylate oligomers and other raw materials, the problems of poor adhesion and poor weather resistance in the material bonding process in the prior art are solved, and efficient and diversified glue filling processes and excellent bonding performance are achieved.
Patent Information
- Application Number
- CN202411679156.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-28
AI Technical Summary
During the bonding process of material, existing ultraviolet curing glues are prone to problems such as poor interface bonding, cracking and degumming after curing, poor waterproofing, weather resistance, wear resistance, and impact resistance.
Modified polyurethane acrylate oligomers are used as the main component, combined with raw materials such as acrylate oligomers, diluents, photoinitiators, coupling agents and carbon black, and prepare ultraviolet adhesives through multiple reactions to improve their interaction and adhesion with the substrate.
It realizes efficient bonding of ultraviolet adhesives in diversified adhesive application processes, with strong interfacial adhesion, low curing and shrinkage, good flexibility, light shielding and light transmission, high waterproofness and high wear resistance.
Smart Images

Figure CN119709100A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of adhesives, and in particular to ultraviolet adhesives and a preparation method and application thereof. Background Art
[0002] Under the requirements of energy-saving and environmental protection policies, material bonding also requires the use of more efficient and energy-saving processes. UV curing adhesive is widely used in the field of material bonding due to its fast curing speed, high bonding strength, no solvent, odorless and non-toxic characteristics, and is applied to a variety of products such as mobile phones, computers, smart wearables and other electronic devices. By applying UV curing adhesive to the material to be bonded and irradiating the adhesive with UV light, a strong bond can be quickly formed. The bonded material is stable and will not cause thermal effects on the bonding area.
[0003] In the prior art, during the material bonding process, problems such as poor interface adhesion, cracking and debonding after bonding and curing, poor waterproof performance, poor weather resistance, wear resistance, and poor impact resistance are likely to occur; and after the material is bonded, local warping deformation, stress cracking and debonding, and low substrate adhesion may occur, which will affect the service life of the bonded material, causing waste of resources and economic losses. Summary of the invention
[0004] In view of this, the present invention proposes a UV adhesive and a preparation method and application thereof, aiming to realize that the UV adhesive is applicable to a variety of sizing processes, has strong interface adhesion, low curing shrinkage, good flexibility, certain light-shielding and light-transmittance, high waterproofness, and high wear resistance.
[0005] The UV adhesive proposed in the first aspect of the present invention comprises the following raw material components in weight percentage: 50% to 75% of modified polyurethane acrylate oligomer; 10% to 20% of acrylate oligomer; 10% to 20% of diluent; 3% to 5% of photoinitiator; 1% to 3% of coupling agent; and 1% to 2% of carbon black; wherein the modified polyurethane acrylate oligomer is obtained by multi-step reaction of diols, toluene diisocyanate, inhibitor and hydroxyethyl methacrylate.
[0006] It can be seen from the above technical scheme that the UV adhesive proposed in the first aspect of the present invention contains more polycarbonate segments on the modified polyurethane acrylate oligomer, so that the solubility parameter of the adhesive body is as close as possible to the substrate, so that the intermolecular interaction between the UV adhesive and the substrate is more likely to occur; the modified polyurethane acrylate oligomer also contains more diol segments, which improves the adhesion of the UV adhesive, has greater strength after being connected to the substrate, is not easy to shrink and deform, and improves the weather resistance and wear resistance of the UV adhesive. Acrylate oligomers and modified polyurethane acrylate oligomers have good compatibility, and acrylate oligomers can further improve the weather resistance of the entire UV adhesive and enhance the adhesion of the UV adhesive to different substrates. After absorbing ultraviolet light, the photoinitiator can cause each monomer to react, so that the UV adhesive can be quickly cured after receiving ultraviolet light. Diluents can adjust the concentration and viscosity of the raw materials of UV adhesives when mixed, making the mixture easy to use and apply, and can increase the number of side chains of UV adhesives and improve the flexibility of UV adhesives. Coupling agents can also increase the adhesion of UV adhesives to substrates. Carbon black can adjust the color of UV adhesives, making them more compatible with the substrate after curing or providing certain light-shielding and light-transmitting properties, thereby improving the use function of UV adhesives.
[0007] In some embodiments, the diols include: at least one of polypropylene carbonate diol, polycarbonate diol and polyester diol; and / or, the inhibitor includes p-hydroxyanisole and / or hydroquinone.
[0008] In some embodiments, the modified polyurethane acrylate oligomer is prepared by the following steps: dissolving diols in ethyl acetate solvent to form a diol solution; adding toluene diisocyanate into a container, and adding the diol solution to react at a temperature of 40°C to 45°C for 2h to 4h; then adding an inhibitor, a catalyst and hydroxyethyl methacrylate to the solution after the insulation reaction to react at a reaction temperature of 65°C to 70°C for 4h to 6h; after the reaction is completed, removing the ethyl acetate solvent in the solution to obtain the modified polyurethane acrylate oligomer.
[0009] In some embodiments, the diols include a mixture of polypropylene carbonate diol, polycarbonate diol and polyester diol, and the mass ratio of polypropylene carbonate diol, polycarbonate diol and polyester diol is (1.5-2.5):(1.5-2.5):(0.5-1.5); and / or, the mass ratio of the diols, the toluene diisocyanate, the inhibitor and the hydroxyethyl methacrylate is (35-65):(20-40):(0.01-0.02):(8-13) and / or, the catalyst is a 0.05% organic bismuth catalyst.
[0010] In some embodiments, the glass transition temperature of the acrylate oligomer is 25°C to 85°C; and / or, the viscosity of the acrylate oligomer is 10cps to 30,000cps; and / or, the functionality of the modified polyurethane acrylate oligomer is 2; and / or, the viscosity of the modified polyurethane acrylate oligomer is 20,000cps to 40,000cps.
[0011] In some embodiments, the diluent includes: hydroxyethyl acrylate, hydroxyethyl methacrylate, 1,6-hexanediol diacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, propoxylated neopentyl glycol diacrylate, propoxylated glycerol triacrylate, ethoxylated trimethylolpropane triacrylate, cyclotrimethylolpropane formal acrylate, 4-hydroxybutyl acrylate, dicyclopentadiene methacrylate, tetrahydrofuran methacrylate, tetrahydrofuran acrylate, 4-tert-butylcyclohexyl acrylate, 4-acryloylmorpholine, trimethylcyclohexyl acrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate, or a mixture of two or more thereof.
[0012] In some embodiments, the photoinitiator includes: 2-hydroxy-2-methyl-1-phenyl-1-propanone, triarylsulfonium salt cationic photoinitiator, 1-hydroxycyclohexyl phenyl ketone, diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide, 2,4,6-trimethylbenzoyl phenylphosphonic acid ethyl ester, 1,1'-(methylene di-4,1-phenylene) bis [2-hydroxy-2-methyl-1-propanone], 2-phenylbenzyl-2-dimethylamine-1-(4-morpholinobenzylphenyl) ) butanone, 2-isopropylthioxanthone, benzoin dimethyl ether, phenyl bis(2,4,6-trimethylbenzoyl)phosphine oxide, diphenyl sulfide disulfone, methyl benzoylformate, arylsulfonium salts, diaryliodonium salts, 9,10-dibutoxyanthracene, 9,10-diethoxyanthracene, a mixture of triarylsulfonium hexafluoroantimonate, and 4-isobutylphenyl-4'-methylphenyliodonium hexafluorophosphate; and / or the absorption wavelength of the photoinitiator is 220nm to 400nm.
[0013] In some embodiments, the coupling agent is γ-(methacryloyloxy)propyl trimethoxysilane, γ-aminopropyl triethoxysilane, γ-(2,3-epoxypropyloxy)propyl trimethoxysilane, γ-mercaptopropyl trimethoxysilane, γ-mercaptopropyl triethoxysilane, vinyl tri(2-methoxyethoxy)silane, vinyl tri(2-methoxyethoxy)silane, γ-(methacryloyloxy)propyl triethoxysilane, methacryloyloxy One or more of methyltriethoxysilane, 3-methacryloxypropyltri(methoxyethoxy)silane, methacryloxypropyltri(dimethylsiloxy)silane, γ-(acryloxy)propyltrimethoxysilane, γ-(acryloxy)propyltriethoxysilane, allyltri(trimethylsiloxy)silane, γ-(β-aminoethyl)aminopropyltrimethoxysilane, anilinemethyltrimethoxysilane, and γ-ureapropyltriethoxysilane.
[0014] The preparation method of the ultraviolet adhesive proposed in the second aspect of the present invention comprises the following steps: adding 50 to 75 parts of modified polyurethane acrylate oligomer, 10 to 20 parts of acrylate oligomer, and 10 to 20 parts of diluent into a container for the first stirring to dissolve and obtain a uniform solution; then adding 3 to 5 parts of photoinitiator, 1 to 3 parts of coupling agent, and 1 to 2 parts of carbon black for the second stirring; standing and filtering to obtain the ultraviolet adhesive.
[0015] It can be seen from the above technical scheme that the preparation method of the UV adhesive proposed in the second aspect of the present invention can achieve the preparation of the UV adhesive by mixing, stirring and reacting the monomers according to the above method, and the preparation method is simple; the prepared UV adhesive is a black viscous liquid, which is convenient to apply, can absorb ultraviolet rays and cure faster, and has high curing efficiency; the cured UV adhesive has good viscosity, high hardness, good tensile strength, shear strength and good weather resistance.
[0016] In some embodiments, during the first stirring, the mixture is slowly stirred at a speed of 300 r / min to 600 r / min for 10 min to 20 min, and then stirred at a speed of 900 r / min to 1100 r / min for 50 min to 70 min, and the reaction temperature is 21°C to 25°C; and / or, during the second stirring, the stirring time is controlled at 20 min to 40 min, and the reaction temperature is controlled at 21°C to 25°C; and / or, the standing time is 20 min to 40 min; and / or, pressure filtration is used during filtration; and / or, the pore size of the filter during filtration is less than or equal to 5 μm.
[0017] The third aspect of the present invention provides an application of the UV adhesive, wherein the UV adhesive is used for bonding polycarbonate materials.
[0018] It can be seen from the above technical scheme that the application of the UV adhesive proposed in the third aspect of the present invention has a group with good affinity for the polycarbonate material. When the UV adhesive is cured, it can generate extremely strong adhesion between the polycarbonate material; the UV adhesive also contains a variety of side chains to increase the molecular toughness and function, so that the UV adhesive is not easy to produce thermal deformation during the curing process, and the polycarbonate material will not warp, curl, or stress deform; after curing, the UV adhesive can also produce a certain light-shielding performance for the bonded polycarbonate material, which can effectively prevent light leakage.
[0019] It should be understood that the above general description and the following detailed description are exemplary and explanatory only and are not restrictive of the disclosure of the embodiments of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained like these accompanying drawings without paying any creative work.
[0021] Figure 1 It is a schematic diagram of the preparation method of the modified polyurethane acrylate oligomer proposed in some embodiments of the present invention.
[0022] Figure 2 It is a schematic diagram of a method for preparing a UV adhesive proposed in some embodiments of the present invention. DETAILED DESCRIPTION
[0023] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, other embodiments obtained by ordinary technicians in this field without creative work are all within the scope of protection of the present invention.
[0024] It should also be understood that the terms used in this application specification are only for the purpose of describing specific embodiments and are not intended to limit the application. As used in this application specification and the appended claims, unless the context clearly indicates otherwise, the singular forms "a", "an" and "the" are intended to include plural forms.
[0025] It should be further understood that the term "and / or" used in the present specification and the appended claims refers to any combination and all possible combinations of one or more of the associated listed items, and includes these combinations. In the absence of conflict, the following embodiments and features in the embodiments may be combined with each other.
[0026] The existing commercially available UV (Ultraviolet) glue has poor bonding force during bonding, and the glue is prone to cracking and debonding after UV aging. After curing, it has poor waterproof and water resistance, poor weather resistance, poor wear resistance, and poor impact resistance, making the overall performance of the entire UV glue generally poor.
[0027] In view of this, an embodiment of the present invention proposes a UV adhesive, comprising the following raw material components in weight percentage: 50% to 75% of modified polyurethane acrylate oligomer; 10% to 20% of acrylate oligomer; 10% to 20% of diluent; 3% to 5% of photoinitiator; 1% to 3% of coupling agent; 1% to 2% of carbon black; wherein the modified polyurethane acrylate oligomer is obtained by multi-step reaction of diols, toluene diisocyanate, inhibitor and hydroxyethyl methacrylate.
[0028] As can be seen from the above technical solution, the UV adhesive proposed by the present invention contains more polycarbonate segments on the modified polyurethane acrylate oligomer in the range of 50% to 75% by weight, so that the solubility parameter of the adhesive body is as close as possible to the substrate, so that the UV adhesive and the substrate are more likely to have intermolecular interaction forces; the modified polyurethane acrylate oligomer also contains more diol segments, which improves the adhesion of the UV adhesive, has greater strength after connection with the substrate, is not easy to shrink and deform, and improves the weather resistance and wear resistance of the UV adhesive. Below the above range, the affinity and interaction between the UV adhesive and the substrate will be reduced; above the above range, the number and types of side chains are less.
[0029] The acrylate oligomer has good compatibility with the modified polyurethane acrylate oligomer and increases the polarity of the molecular system. The acrylate oligomer in the weight percentage range of 10% to 20% can further improve the weather resistance of the entire UV adhesive and enhance the adhesion of the UV adhesive to different substrates. A weight percentage below or above the above range is not conducive to improving the adhesion of the UV adhesive.
[0030] The diluent with a weight percentage of 10% to 20% can adjust the concentration and viscosity of the raw materials of the UV adhesive when mixed, making the mixture easy to use and apply, and can increase the number of side chains of the UV adhesive and improve the flexibility of the UV adhesive. If it is lower than the above range, it will be too concentrated and difficult to apply, the fluidity will be too low, and the UV adhesive will have fewer side chains and fewer types; if it is higher than the above range, the curing efficiency will be affected.
[0031] The photoinitiator with a weight percentage of 3% to 5% can make each monomer react after absorbing ultraviolet light, so that the ultraviolet adhesive can be quickly cured after receiving ultraviolet light. If it is lower than the above range, fewer free radicals will be generated under light, which will make the ultraviolet curing process slower or even unable to effectively cure; if it is higher than the above range, the curing process will be faster and the reaction will be difficult to control.
[0032] The coupling agent in the weight percentage range of 1% to 3% can also increase the adhesion of the UV adhesive to the substrate, so that the UV adhesive and the substrate have sufficient adhesion. If the UV adhesive is below the above range, the adhesion of the UV adhesive is insufficient, and if it is above the above range, the cost is high, the viscosity is large, and it is not easy to apply.
[0033] The carbon black in the weight percentage range of 1% to 2% can adjust the color of the UV adhesive, so that the UV adhesive can be more compatible with the substrate after curing or provide a certain light shielding and light transmittance, thereby improving the use function of the UV adhesive. If it is too low below the above range, the color of the UV adhesive cannot be effectively adjusted, and if it is too high above the above range, the light transmittance is insufficient.
[0034] The main body of the UV adhesive of the present invention has more side chains, which increases the distance between molecules and can well reduce the volume shrinkage caused by curing and cross-linking, so that the UV adhesive of the present invention has very low curing shrinkage.
[0035] In summary, the raw materials of the UV adhesive proposed in the present invention have good compatibility with each other, and the characteristics of each raw material after mixing can be fully reflected. The obtained UV adhesive has good interface adhesion, good weather resistance, water resistance, high mechanical strength and wear resistance, and low curing shrinkage.
[0036] It can be understood that compared with the shortcomings of UV adhesives in the prior art, such as poor interfacial adhesion, cracking and degumming of the glue after UV curing, poor waterproof and water-resistant properties, and poor weather resistance, wear resistance and impact resistance, the UV adhesive of the present invention overcomes the above shortcomings and has excellent comprehensive performance.
[0037] In an optional example, the UV adhesive may include the following components in weight percentage: 50% modified polyurethane acrylate oligomer, 20% acrylate oligomer, 20% diluent, 5% photoinitiator, 3% coupling agent, and 2% carbon black.
[0038] In an optional example, the UV adhesive may include the following components in weight percentage: 60% modified polyurethane acrylate oligomer, 15% acrylate oligomer, 18% diluent, 4% photoinitiator, 1% coupling agent, and 2% carbon black.
[0039] In an optional example, the UV adhesive may include the following components in weight percentage: 63% modified polyurethane acrylate oligomer, 15% acrylate oligomer, 15% diluent, 3.5% photoinitiator, 2% coupling agent, and 1.5% carbon black.
[0040] In an optional example, the UV adhesive may include the following components in weight percentage: 67% modified polyurethane acrylate oligomer, 12% acrylate oligomer, 13% diluent, 4% photoinitiator, 3% coupling agent, and 1% carbon black.
[0041] In an optional example, the UV adhesive may include the following components in weight percentage: 70% modified polyurethane acrylate oligomer, 10% acrylate oligomer, 14% diluent, 4% photoinitiator, 1% coupling agent, and 1% carbon black.
[0042] In an optional example, the UV adhesive may include the following components in weight percentage: 75% modified polyurethane acrylate oligomer, 10% acrylate oligomer, 10% diluent, 3% photoinitiator, 1% coupling agent, and 1% carbon black.
[0043] In some embodiments of the present invention, the diols include: at least one of polypropylene carbonate diol, polycarbonate diol and polyester diol. The introduction of polypropylene carbonate diol and polycarbonate diol can introduce a large number of polycarbonate unit structures into the UV adhesive, including bio-based polypropylene carbonate segments and conventional polycarbonate segments. These segments are similar to the substrate properties of polycarbonate materials, especially the solubility parameters are similar, and good hydrogen bonds, van der Waals forces and other effects can be generated between molecules. In addition, some physical action modes make the UV adhesive with polycarbonate unit structure and the substrate of polycarbonate materials produce strong interfacial adhesion. The introduction of polyester diol can introduce more polyester diol segments into the UV adhesive, so that it has high initial adhesion to polar substrates, and improves the adhesion and bulk strength of the UV adhesive.
[0044] In some embodiments of the present invention, the inhibitor comprises p-hydroxyanisole and / or hydroquinone. The inhibitor can effectively control the degree of polymerization reaction in the reaction process, so that the reaction will not be too violent and the partial reaction is terminated, and the reaction process is controllable. P-hydroxyanisole and hydroquinone are phenol inhibitors, which can be oxidized into corresponding quinones in the reaction, and quinones are combined with the free radicals of the chain to inhibit polymerization, and their low price makes the manufacturing cost low.
[0045] In some embodiments of the present invention, Figure 1 As shown, the modified polyurethane acrylate oligomer is prepared by the following steps:
[0046] Step S110, dissolving the diols into a diol solution using ethyl acetate solvent, so that the concentration of the diol solution is appropriate, and multiple diols can be mixed evenly with each other, which is convenient for subsequent reactions and convenient for removing the ethyl acetate solvent after the subsequent reactions are completed.
[0047] Optionally, the diols are the aforementioned diols, which will not be described in detail here.
[0048] Advantageously, the diols include a mixture of polypropylene carbonate diol, polycarbonate diol and polyester diol, and the mass ratio of polypropylene carbonate diol, polycarbonate diol and polyester diol is (1.5-2.5):(1.5-2.5):(0.5-1.5), so that the diol solution is formed into a mixed solution of multiple diol solutions, which can have the chemical properties of each diol substance. For example, the mass ratio of polypropylene carbonate diol, polycarbonate diol and polyester diol is 1.5:1.5:0.5; or, the mass ratio of polypropylene carbonate diol, polycarbonate diol and polyester diol is 2:2:1; or, the mass ratio of polypropylene carbonate diol, polycarbonate diol and polyester diol is 2.5:2.5:1.5.
[0049] Step S120, adding toluene diisocyanate into a container, and adding a diol solution to react at a temperature of 40°C to 45°C for 2h to 4h, thereby forming a compound with a carbamate structure, and making the synthesized molecule have carbon dioxide-based and bio-based modified carbamate segments and acrylate segments.
[0050] Illustratively, the reaction temperature of toluene diisocyanate and diol solution is 40°C, 41°C, 42°C, 43°C, 44°C or 45°C.
[0051] Exemplarily, the reaction time of toluene diisocyanate and diol solution is 2 h, 2.5 h, 3 h, 3.5 h, or 4 h.
[0052] Step S130, adding a polymerization inhibitor, a catalyst and hydroxyethyl methacrylate to the solution after the insulation reaction to react, the reaction temperature is 65°C to 70°C (for example, the reaction temperature can be 65°C, 66°C, 67°C, 68°C, 69°C or 70°C), and the reaction time is 4h to 6h (for example, the reaction time is 4h, 4.5h, 5h, 5.5h or 6h). The polymerization inhibitor, catalyst and hydroxyethyl methacrylate here react with the compound with a carbamate structure generated in the reaction of step S120 to generate a solution with a modified polyurethane acrylate oligomer.
[0053] It should be noted here that the inhibitors are of the types mentioned above, which will not be described in detail here.
[0054] Optionally, the catalyst is a 0.05% organic bismuth catalyst. By adding the catalyst, the reaction can be carried out efficiently. The organic bismuth can also be quickly mixed with other organic solvents and dispersed evenly, and the catalytic effect is good.
[0055] Step S140: After the reaction is completed, the ethyl acetate solvent in the solution is removed to obtain a modified polyurethane acrylate oligomer. Removing the ethyl acetate solvent can increase the concentration and viscosity of the modified polyurethane acrylate oligomer, making it convenient to further prepare a UV adhesive with other reactive monomers.
[0056] Optionally, the mass ratio of diols, toluene diisocyanate, inhibitor and hydroxyethyl methacrylate is (35-65): (20-40): (0.01-0.02): (8-13). When the mass ratio is within the above range, the materials of each reactant are saved, the reaction rate is controllable, and the yield rate of the desired modified polyurethane acrylate oligomer is high. For example, the mass ratio of diols, toluene diisocyanate, inhibitor and hydroxyethyl methacrylate is 35:20:0.01:8; for another example, the mass ratio of diols, toluene diisocyanate, inhibitor and hydroxyethyl methacrylate is 50:30:0.012:11.5; for another example, the mass ratio of diols, toluene diisocyanate, inhibitor and hydroxyethyl methacrylate is 65:40:0.02:13.
[0057] Advantageously, the modified polyurethane acrylate oligomer prepared above has a functionality of 2, and the modified polyurethane acrylate oligomer prepared is a colorless or slightly yellow viscous liquid.
[0058] Advantageously, the viscosity of the modified polyurethane acrylate oligomer prepared above is 20,000 cps to 40,000 cps (60° C.). It can be seen that the viscosity of the modified polyurethane acrylate oligomer is relatively large, which is beneficial to improving the viscosity of the UV adhesive.
[0059] In some embodiments of the present invention, the glass transition temperature of the acrylate oligomer is 25° C. to 85° C. Optionally, the viscosity of the acrylate oligomer is 10 cps to 30,000 cps, so the acrylate oligomer has a certain viscosity and a certain polarity, which can enhance the adsorption of the UV adhesive to the substrate.
[0060] Optionally, the acrylate oligomer of the present invention is purchased from one or more of 6533B-40, 6536-1, DR-A801, DR-815, DR-A830, DR-A832 of Changxing Materials; MIRAMER SC9211, MIRAMER SC9060 of Meiyuan.
[0061] In some embodiments of the present invention, the diluent includes: hydroxyethyl acrylate, hydroxyethyl methacrylate, 1,6-hexanediol diacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, propoxylated neopentyl glycol diacrylate, propoxylated glycerol triacrylate, ethoxylated trimethylolpropane triacrylate, cyclotrimethylolpropane methyl acrylate, 4-hydroxybutyl acrylate, dicyclopentadiene methacrylate, tetrahydrofuran methacrylate, tetrahydrofuran acrylate, 4-tert-butyl cyclohexyl acrylate, 4-acryloylmorpholine, trimethylcyclohexyl acrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate, or a mixture of two or more thereof. These diluents have good compatibility with other raw material components. They can not only adjust and dilute the mixture to make the concentration and viscosity of the mixture appropriate, but also polymerize on the side chains of modified polyurethane acrylate oligomers during the curing reaction to form UV adhesives with more diverse functions, making the UV adhesive more flexible after curing and the colloid less likely to crack after curing.
[0062] In some embodiments of the present invention, the photoinitiator includes: 2-hydroxy-2-methyl-1-phenyl-1-propanone (abbreviated as 1173), triarylsulfonium salt cationic photoinitiator (abbreviated as 1176), 1-hydroxycyclohexyl phenyl ketone (abbreviated as 184), diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide (abbreviated as TPO), 2,4,6-trimethylbenzoyl phenylphosphonic acid ethyl ester (abbreviated as TPO-L), 1,1'-(methylene di-4,1-phenylene) bis[2-hydroxy-2-methyl-1-propanone] (abbreviated as 127), 2-phenylbenzyl-2-dimethyl Amine-1-(4-morpholinobenzylphenyl)butanone (referred to as 369), 2-isopropylthioxanthone (referred to as ITX), benzoin dimethyl ether (referred to as BDK), phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (referred to as 819), diphenyl sulfide disulfone (referred to as 754), methyl benzoylformate (referred to as MBF), arylsulfonium salts, diaryliodonium salts (referred to as IK-1), 9,10-dibutoxyanthracene (referred to as UVS-1331), 9,10-diethoxyanthracene (referred to as UVS-1101), triarylsulfonium hexafluoroantimonate mixture (referred to as Easepi 1176), 4-isobutylphenyl-4'-methylphenyliodonium hexafluorophosphate (referred to as Easepi 250) One or more of them. When these photoinitiators are irradiated by light sources, they can be quickly activated and generate active free radicals, which then trigger further reactions between the substances in the UV adhesive to achieve rapid curing.
[0063] Among them, some photoinitiators such as arylsulfonium salts include CPI-100P (purchased from Japan Sanyo), CPI-101A (purchased from Japan Sanyo), CPI-200K (purchased from Japan Sanyo), CPI-210S (purchased from Japan Sanyo), CPI-310B (purchased from Japan Sanyo), CPI-410S (purchased from Japan Sanyo), Easepi 6992 (purchased from Shanghai Guangyi Chemical). Diaryliodonium salts such as IK-1 were purchased from Japan Sanyo.
[0064] In some examples, the absorption wavelength of the photoinitiator is 220 nm to 400 nm. The photoinitiator can be excited and activated under the illumination of ultraviolet light of the above wavelength, so that the photoinitiator can start the polymerization reaction of various substances in the ultraviolet adhesive under the illumination condition.
[0065] In some embodiments, the coupling agent is γ-(methacryloyloxy)propyl trimethoxysilane, γ-aminopropyl triethoxysilane, γ-(2,3-epoxypropyloxy)propyl trimethoxysilane, γ-mercaptopropyl trimethoxysilane, γ-mercaptopropyl triethoxysilane, vinyl tri(2-methoxyethoxy)silane, vinyl tri(2-methoxyethoxy)silane, γ-(methacryloyloxy)propyl triethoxysilane, methacryloyloxymethyl One or more of triethoxysilane, 3-methacryloxypropyl tri(methoxyethoxy)silane, methacryloxypropyl tri(dimethylsiloxy)silane, γ-(acryloxy)propyl trimethoxysilane, γ-(acryloxy)propyl triethoxysilane, allyl tri(trimethylsiloxy)silane, γ-(β-aminoethyl)aminopropyl trimethoxysilane, aniline methyl trimethoxysilane, and γ-urea propyl triethoxysilane. These coupling agents can also increase the adhesion of the UV adhesive to the substrate, so that the cured UV adhesive has sufficient adhesion to the substrate to prevent debonding.
[0066] The preparation method of the UV adhesive of the present invention is described below.
[0067] According to the method for preparing the UV adhesive of each of the above embodiments proposed in the embodiments of the present invention, Figure 2 As shown, the following steps are included:
[0068] Step S210, adding 50 to 75 parts of modified polyurethane acrylate oligomer, 10 to 20 parts of acrylate oligomer, and 10 to 20 parts of diluent into a container, stirring for the first time, dissolving and obtaining a uniform solution.
[0069] Optionally, during the first stirring, stir at a low speed first and then at a high speed. For example, in some specific examples, stir slowly at a low speed of 300r / min to 600r / min for 10min to 20min, and then stir at a high speed of 900r / min to 1100r / min for 50min to 70min. The low speed and high speed here are relative, and are intended to emphasize that different stages have different stirring speeds. The stirring time can be adjusted according to the actual reaction situation until the reactants are fully mixed and the properties tend to be stable.
[0070] Optionally, the reaction temperature is 21°C to 25°C, for example, 21°C, 22°C, 23°C, 24°C or 25°C. The reaction temperature is relatively mild, which is conducive to uniform mixing.
[0071] Step S220, add 3 to 5 parts of photoinitiator, 1 to 3 parts of coupling agent, and 1 to 2 parts of carbon black and stir for the second time.
[0072] Optionally, during the second stirring, the stirring time is controlled to be 20 min to 40 min. The stirring speed can be the same as the stirring speed used during the first stirring, or can be appropriately slowed down according to the reaction conditions, and there is no specific limitation here.
[0073] Optionally, the reaction temperature is controlled at 21°C to 25°C, for example, 21°C, 22°C, 23°C, 24°C or 25°C. The reaction temperature is relatively mild, which is conducive to uniform mixing; it is also conducive to uniform mixing with the solution after the first stirring, and the temperature difference of the solution is small.
[0074] Step S230, standing and filtering to obtain the ultraviolet adhesive.
[0075] Optionally, the standing time is 20 min to 40 min, so that the reaction product UV adhesive is fully separated from the solution.
[0076] Optionally, pressure filtration is used during filtration, which is beneficial for the reaction products to pass through the filter faster and improve the filtration speed.
[0077] Optionally, the pore size of the filter during filtration is less than or equal to 5 μm, so that the particles of the reaction product after filtration are more uniform, the properties of the ultraviolet adhesive are more uniform, and it is convenient to apply evenly during application, and the application effect is good.
[0078] It should be noted here that the preparation method of the modified polyurethane acrylate oligomer is as described above and will not be repeated here.
[0079] As can be seen from the above technical scheme, the preparation method of the UV adhesive proposed in the present invention can be realized by mixing, stirring and reacting the monomers according to the above method, and the preparation method is simple; the prepared UV adhesive is in the form of a black viscous liquid, which is convenient for application, can absorb ultraviolet rays and solidify faster, and has high curing efficiency; the cured UV adhesive has good viscosity, high hardness, good tensile strength, shear strength and good weather resistance.
[0080] The application of the UV adhesive according to the embodiment of the present invention is described below.
[0081] According to the application of the UV adhesive proposed in the embodiment of the present invention, the UV adhesive is used for bonding polycarbonate materials.
[0082] As can be seen from the above technical scheme, the application of the UV adhesive proposed in the present invention has a group with good affinity to the polycarbonate material. When the UV adhesive is cured, it can generate extremely strong bonding force with the polycarbonate material; the UV adhesive also contains a variety of side chains to increase the molecular toughness and function, so that the UV adhesive is not easy to produce thermal deformation during the curing process, and the polycarbonate material will not warp, curl or stress deformation; after curing, the UV adhesive can also produce a certain light-shielding performance for the bonded polycarbonate material, which can effectively prevent light leakage.
[0083] The preparation method of the UV adhesive of the present invention is further described below in conjunction with specific examples and test data.
[0084] Implementation Case 1
[0085] 1. Preparation of UV Adhesive
[0086] (1) Add 50 g of modified polyurethane acrylate oligomer, 20 g of acrylate oligomer and 20 g of diluent into a container and stir for the first time. Stir slowly at 500 r / min for 15 minutes, then adjust the speed to 1000 r / min and continue stirring for 60 minutes to completely dissolve the system to obtain a uniform solution. During the process, maintain the liquid temperature in the container at about 23°C.
[0087] (2) Then, 5 g of initiator, 3 g of coupling agent and 2 g of carbon black were slowly added and stirred for a second time for 30 minutes, during which the liquid temperature in the container was maintained at about 23°C.
[0088] (3) After stirring, the mixture was allowed to stand for 30 minutes, and then filtered under pressure using a 5 μm organic filter to obtain a black UV adhesive.
[0089] 2. Performance Testing
[0090] Testing instruments: cone-plate rheometer equipment, tensile testing machine, hot and cold shock chamber, high temperature and high humidity chamber;
[0091] The specific test method is as follows:
[0092] 1. Appearance: Encapsulate the resin into a colorless and transparent glass bottle and observe the color properties of the resin outdoors or under white light.
[0093] 2. Viscosity: Turn on the power of the DVNext Cone-Plate Rheometer, start the heating cycle, initialize the equipment and adjust the gap between the rotor and the sample cup. After the temperature rises to 60°C and stabilizes for 2 minutes, put a small amount of resin into the CPA sample cup of the DVNext Cone-Plate Rheometer, install the sample cup after the sample softens and flows, and start the test. After the curve is horizontally stable, record the viscosity data, stop the test, remove the sample cup, wipe the rotor and sample cup clean and put them back in place, and turn off the heating cycle and the power of the equipment.
[0094] 3. Hardness after curing: Slowly introduce the UV adhesive into a transparent mold, and take out the adhesive block after UV curing. Use a digital display Shore D hardness tester to test the hardness on the surface of the adhesive block, test 3 times at different positions, and take the average value as the hardness value of the UV adhesive after curing.
[0095] 4. Tensile strength: Slowly inject the UV adhesive into the pre-prepared standard dumbbell bar mold, then cure it with UV, take out the dumbbell-shaped strip and perform a tensile test on the universal tensile testing machine. Turn on the universal tensile testing machine power and test software, select the material type and set the test parameters; load the standard sample into the test fixture, click the start test button, stop the test after the cured UV adhesive sample is slowly broken, read the tensile strength test results and record them; repeat the test three times, and take the average value as the tensile strength value of the UV adhesive.
[0096] 5. Elongation at break: Slowly inject the UV adhesive into the pre-prepared standard dumbbell bar mold, then cure it with UV, take out the dumbbell-shaped adhesive strip and conduct a tensile test on the universal tensile testing machine. Turn on the power and test software of the universal tensile testing machine, select the material type and set the test parameters; load the standard sample into the tensile test fixture, click the start test button, stop the test after the cured UV adhesive sample is slowly broken, read the elongation at break test results and record them; repeat the test three times, and take the average value as the elongation at break value of the UV adhesive.
[0097] 6. Shear strength: Clean the standard shear test PC sheet, then apply UV adhesive to one end of the sheet, about 1cm wide, overlap another PC sheet, use 0.25mm filaments to control the thickness of the adhesive layer, and then tighten the two ends of the overlap with transparent thin clips. After UV curing, remove the clips, load the sample standard into the shear test fixture, click the start test button, stop the test after the test sample is slowly pulled apart or shifted, read the tensile result and record it; repeat the test three times. According to the following formula:
[0098] T=F / (L*b)
[0099] Calculate the shear strength and take the average value. T refers to the shear strength (in MPa), F refers to the tensile force (in N), L refers to the width of the PC sample (in mm), and b refers to the depth of the UV adhesive applied on the PC sheet (in mm).
[0100] 7. Shear strength (high temperature and high humidity): Clean the standard shear test PC sheet, then apply UV adhesive to one end of the sheet, about 1cm wide, overlap another PC sheet, use 0.25mm filament to control the thickness of the adhesive layer, and then tighten the two ends of the overlap with transparent thin clips. After UV curing, remove the clips and put the cured UV adhesive sample into a high temperature and high humidity box for testing. After the high temperature and high humidity test, place the sample at room temperature for 2 hours, then load the sample standard into the shear test fixture, click the start test button, stop the test after the test sample is slowly pulled apart or shifted, read the tensile result and record it; repeat the test three times. Calculate the shear strength according to the following formula: T = F / (L*b) and take the average value. Where T refers to shear strength (unit MPa), F refers to tensile force (unit N), L refers to the width of the PC sample (unit mm), and b refers to the depth of the UV adhesive applied on the PC sheet (unit mm).
[0101] 8. Shear strength (hot and cold shock): Clean the standard shear test PC sheet, then apply UV adhesive to one end of the sheet, about 1cm wide, overlap another PC sheet, use 0.25mm filaments to control the thickness of the adhesive layer, and then tighten the two ends of the overlap with transparent thin clips. After UV curing, remove the clips and put the UV adhesive sample into the hot and cold shock box for testing. After the hot and cold shock test, place the sample at room temperature for 2 hours, then put the sample standard into the shear test fixture, click the start test button, stop the test after the test sample is slowly pulled apart or shifted, read the tensile result and record it; repeat the test three times. Calculate the shear strength according to the following formula: T = F / (L*b) and take the average value. Where T refers to shear strength (unit MPa), F refers to tensile force (unit N), L refers to the width of the PC sample (unit mm), and b refers to the depth of the UV adhesive applied on the PC sheet (unit mm).
[0102] Table 1 Test performance value table of UV adhesive in Example 1
[0103]
[0104] Implementation Case 2
[0105] 1. Preparation of UV Adhesive
[0106] (1) Add 75 g of modified polyurethane acrylate oligomer, 10 g of acrylate oligomer and 10 g of diluent into a container and stir for the first time. Stir slowly at 500 r / min for 15 minutes, then adjust the speed to 1000 r / min and continue stirring for 60 minutes to completely dissolve the system to obtain a uniform solution. During the process, maintain the liquid temperature in the container at 21°C.
[0107] (2) Then slowly add 3 g of initiator, 1 g of coupling agent and 1 g of carbon black, and continue stirring for 30 minutes, while maintaining the liquid temperature in the container at 21°C.
[0108] (3) After stirring, the mixture was allowed to stand for 30 minutes, and then filtered under pressure using a 5 μm organic filter to obtain a black UV adhesive.
[0109] 2. Performance Testing
[0110] The test instrument and specific test method are the same as in Example 1, and the test results are shown in the following table.
[0111] Table 2 Test performance values of UV adhesive in Example 2
[0112]
[0113] Implementation Case 3
[0114] 1. Preparation of UV Adhesive
[0115] (1) Add 63 g of modified polyurethane acrylate oligomer, 15 g of acrylate oligomer and 15 g of diluent into a container, first slowly stir at 500 r / min for 15 minutes, then adjust the speed to 1000 r / min and continue stirring for 60 minutes to completely dissolve the system to obtain a uniform solution. During the process, maintain the liquid temperature in the container at 25°C.
[0116] (2) Then slowly add 3.5 g of initiator, 2 g of coupling agent and 1.5 g of carbon black and continue stirring for 30 minutes while maintaining the liquid temperature in the container at 25°C.
[0117] (3) After stirring, the mixture was allowed to stand for 30 minutes, and then filtered under pressure using a 5 μm organic filter to obtain a black UV adhesive.
[0118] 2. Performance Testing
[0119] The test instrument and specific test method are the same as in Example 1, and the test results are shown in the following table.
[0120] Table 3 Test performance values of UV adhesive in Example 3
[0121]
[0122] As shown in Tables 1, 2 and 3 above, the UV adhesive of the present invention has a relatively large viscosity, is easy to apply and adhere to the substrate, has high tensile strength, high fracture strength, high hardness after curing, high temperature impact resistance, strong water resistance, and resistance to cold and hot shocks.
[0123] It can be seen that the UV adhesive of the present invention has the following beneficial effects:
[0124] 1. The viscosity of the UV adhesive of the present invention can be appropriately adjusted according to the requirements of different application scenarios, and can meet different gluing processes such as fully automatic dispensing, fully automatic spraying, and manual dispensing.
[0125] 2. A large number of polycarbonate unit structures are introduced into the UV adhesive of the present invention, which has a solubility parameter similar to that of polycarbonate (PC) materials. Hydrogen bonds, van der Waals forces and other interactions can be generated between molecules. Combined with other physical action modes, strong adhesion can be generated at the coated interface.
[0126] 3. The main chain of the UV adhesive of the present invention contains carbon dioxide-based and bio-based modified urethane segments and acrylate segments. The cured UV adhesive has the high wear resistance, flexibility, high tear strength and excellent low-temperature resistance of polyurethane and the excellent optical properties and water resistance of polyacrylic acid, and has good impact resistance as a whole.
[0127] 4. The acrylate oligomer introduced into the UV adhesive of the present invention increases the polarity of the molecular system and enhances the interaction such as adsorption between the UV adhesive molecular system and the substrate, thereby further improving the adhesion of the UV adhesive.
[0128] 5. After curing, the UV adhesive of the present invention contains more side chains on the main chain, which increases the distance between molecules, can well reduce the volume shrinkage caused by curing and cross-linking, and has very low curing shrinkage.
[0129] 6. The UV adhesive of the present invention is particularly suitable for bonding PC materials, and can be widely used for bonding PC components in electronic fields such as mobile phones, computers, and smart wearables. After the UV adhesive is bonded to the PC components, it has good adhesion, is not easy to debond, is not easy to crack, and has high curing efficiency.
[0130] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed by the present invention, and these modifications or replacements should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A UV adhesive, characterized in that: The raw material components include the following weight percentages: Modified polyurethane acrylate oligomer 50% to 75%; Acrylate oligomer 10% to 20%; Diluent 10% to 20%; Photoinitiator 3% to 5%; Coupling agent 1% to 3%; Carbon black 1% to 2%; The modified polyurethane acrylate oligomer is obtained by multi-step reaction of diols, toluene diisocyanate, inhibitor and hydroxyethyl methacrylate.
2. The UV adhesive according to claim 1, characterized in that: The diols include: at least one of polypropylene carbonate diol, polycarbonate diol and polyester diol; and / or, The polymerization inhibitor includes p-hydroxyanisole and / or hydroquinone.
3. The UV adhesive according to claim 1 or 2, characterized in that: The modified polyurethane acrylate oligomer is prepared by the following steps: Dissolving diols in ethyl acetate solvent to obtain diol solution; Add toluene diisocyanate into a container, and then add a diol solution and react at a temperature of 40°C to 45°C for 2h to 4h; Then, adding a polymerization inhibitor, a catalyst and hydroxyethyl methacrylate to the solution after the heat preservation reaction to carry out the reaction at a temperature of 65° C. to 70° C. for a reaction time of 4 h to 6 h; After the reaction is completed, the ethyl acetate solvent in the solution is removed to obtain the modified polyurethane acrylate oligomer.
4. The UV adhesive according to claim 3, characterized in that: The diols include a mixture of polypropylene carbonate diol, polycarbonate diol and polyester diol, and the mass ratio of polypropylene carbonate diol, polycarbonate diol and polyester diol is (1.5-2.5):(1.5-2.5):(0.5-1.5); and / or, The mass ratio of the diol, the toluene diisocyanate, the polymerization inhibitor and the hydroxyethyl methacrylate is (35-65): (20-40): (0.01-0.02): (8-13); and / or, The catalyst is a 0.05% organic bismuth catalyst.
5. The UV adhesive according to claim 1, characterized in that: The glass transition temperature of the acrylate oligomer is 25° C. to 85° C.; and / or, the viscosity of the acrylate oligomer is 10 cps to 30,000 cps; and / or, the functionality of the modified polyurethane acrylate oligomer is 2; and / or, the viscosity of the modified polyurethane acrylate oligomer is 20,000 cps to 40,000 cps.
6. The UV adhesive according to claim 1, characterized in that: The diluent includes: one or a mixture of two or more of hydroxyethyl acrylate, hydroxyethyl methacrylate, 1,6-hexanediol diacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, propoxylated neopentyl glycol diacrylate, propoxylated glycerol triacrylate, ethoxylated trimethylolpropane triacrylate, cyclotrimethylolpropane formal acrylate, 4-hydroxybutyl acrylate, dicyclopentadiene methacrylate, tetrahydrofuran methacrylate, tetrahydrofuran acrylate, 4-tert-butyl cyclohexyl acrylate, 4-acryloylmorpholine, trimethylcyclohexyl acrylate, trimethylolpropane triacrylate, and pentaerythritol triacrylate.
7. The UV adhesive according to claim 1, characterized in that: The photoinitiator includes: 2-hydroxy-2-methyl-1-phenyl-1-propanone, triarylsulfonium salt cationic photoinitiator, 1-hydroxycyclohexyl phenyl ketone, diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide, 2,4,6-trimethylbenzoyl phenylphosphonic acid ethyl ester, 1,1'-(methylene di-4,1-phenylene) bis [2-hydroxy-2-methyl-1-propanone], 2-phenylbenzyl-2-dimethylamine-1- (4-morpholinobenzylphenyl)butanone, 2-isopropylthioxanthone, benzoin dimethyl ether, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, diphenyl sulfide disulfone, methyl benzoylformate, arylsulfonium salts, diaryliodonium salts, 9,10-dibutoxyanthracene, 9,10-diethoxyanthracene, a mixture of triarylsulfonium hexafluoroantimonates, and 4-isobutylphenyl-4'-methylphenyliodonium hexafluorophosphate; and / or, The absorption wavelength of the photoinitiator is 220nm-400nm.
8. The UV adhesive according to claim 1, characterized in that: The coupling agent is one or more of γ-(methacryloyloxy)propyl trimethoxysilane, γ-aminopropyl triethoxysilane, γ-(2,3-epoxypropyloxy)propyl trimethoxysilane, γ-mercaptopropyl trimethoxysilane, γ-mercaptopropyl triethoxysilane, vinyl tri(2-methoxyethoxy)silane, vinyl tri(2-methoxyethoxy)silane, γ-(methacryloyloxy)propyl triethoxysilane, methacryloxymethyl triethoxysilane, 3-methacryloyloxypropyl tri(methoxyethoxy)silane, methacryloxypropyl tri(dimethylsiloxy)silane, γ-(acryloyloxy)propyl trimethoxysilane, γ-(acryloyloxy)propyl triethoxysilane, allyl tri(trimethylsiloxy)silane, γ-(β-aminoethyl)aminopropyl trimethoxysilane, aniline methyl trimethoxysilane, and γ-ureapropyl triethoxysilane.
9. A method for preparing a UV adhesive as claimed in any one of claims 1 to 8, characterized in that: The steps include: Add 50 to 75 parts of modified polyurethane acrylate oligomer, 10 to 20 parts of acrylate oligomer, and 10 to 20 parts of diluent into a container and stir for the first time to dissolve and obtain a uniform solution; Then add 3 to 5 parts of photoinitiator, 1 to 3 parts of coupling agent, and 1 to 2 parts of carbon black and stir for the second time; The ultraviolet adhesive is obtained by standing and filtering.
10. The method for preparing the UV adhesive according to claim 9, characterized in that: During the first stirring, the mixture is first stirred slowly at a speed of 300 r / min to 600 r / min for 10 to 20 min, and then stirred at a speed of 900 r / min to 1100 r / min for 50 to 70 min, and the reaction temperature is 21° C. to 25° C.; and / or, During the second stirring, the stirring time is controlled at 20 min to 40 min, and the reaction temperature is controlled at 21° C. to 25° C.; and / or, The standing time is 20 to 40 minutes; and / or, Filtration using pressure filtration; and / or, The pore size of the filter during filtration is less than or equal to 5 μm.
11. An application of a UV adhesive, characterized in that: The ultraviolet adhesive is used for bonding polycarbonate materials.